Laser and GTAW torch processing of Fe–Cr–B coatings on steel. (February 2015) - Idriss, A. N. Md.; Mridha, S.; Baker, T. N.
<x content-type="archive" xml:space="preserve">Abstract</x> A comparison has been made of the relationship between microstructure and microhardness developed by surface melting Nanosteel SHS 7170 Fe–Cr–B alloy powder onto a plain carbon steel surface. This powder was initially developed as a high velocity oxyfuel sprayed coating, giving a strength 10 times that of mild steel, and is particularly suitable for surface protection against wear and corrosion. In the present study, the alloy powder was injected into the laser melted surface, while a preplaced powder was melted using the gas tungsten arc welding (GTAW) technique. The laser track consisted of fine dendrites and needle-like microstructures, which produced a maximum hardness value of over 800 HV, while the GTAW track produced a mixture of equiaxed and columnar grain microstructures with a maximum hardness value of 670 HV. The lower hardness values are considered to be associated with dilution and grain size.